Pentingnya Perekrutan Berbasis Kompetensi - Teguh Iman Santoso; Riski Taufik Hidayah (Journal of Community Service and Engagement, 2022)
The importance of Competency-based recruitment. Many of the MSMEs that stood up finally had to close because they were not managed by the right people. This is due from the beginning, which is an improper recruitment process that is not competency-based. This counseling activity aims to raise awareness that how important competency-based recruitment is to the sustainability of existing MSME businesses. The method used is to bring in one of the MSME coordinators in Cimahi city, namely Parakarsa Design Resources, to gather the fostered MSMEs (40 people) in a training and provide training on November 16, 2022 on how important competency-based recruitment is compared to existing recruitment. The expected result is the emergence of awareness among the MSMEs assisted by PDR about the importance of competency-based recruitment